Global Burden, Incidence and Disability-Adjusted Life-Years for Dermatitis: A Systematic Analysis Combined With Socioeconomic Development Status, 1990–2019 - Xue, Yi; Bao, Wu; Zhou, Jie; Zhao, Qing-Liang; Hong, Su-Zhuang; Ren, Jun; Yang, Bai-Cheng; Wang, Peng; Yin, Bin; Chu, Cheng-Chao; Liu, Gang; Jia, Chi-Yu (Frontiers in Cellular and Infection Microbiology, 2022)
Background Dermatitis is an important global health problem that not only affects social interaction and physical and mental health but also causes economic burden. Health problems or distress caused by dermatitis may be easily overlooked, and relevant epidemiological data are limited. Therefore, a better understanding of the burden of dermatitis is necessary for developing global intervention strategies. Methods All data on dermatitis, including atopic dermatitis (AD), contact dermatitis (CD) and seborrhoeic dermatitis (SD), were obtained from the Global Burden of Disease 2019 (GBD2019) database. The extracted age-standardized incidence rates (ASIR) and disability-adjusted life-years (DALYs) rates (ASDR) data were analysed by stratification, including by sex, country or region, and sociodemographic index (SDI) indicators. Finally, we analysed the correlation between the global burden of dermatitis and socioeconomic development status. Results According to the GBD 2019 estimate, the ASIR and ASDR for the three major types of dermatitis in 2019 were 5244.3988 (95% CI 4551.7244–5979.3176) per 100,000 person-years and 131.6711 (95% CI 77.5876–206.8796) per 100,000 person-years. The ASIR and ASDR of atopic dermatitis, contact dermatitis and seborrhoeic dermatitis are: Incidence (95%CI,per 100,000 person-years), 327.91 (312.76-343.67), 3066.04 (2405.38-3755.38), 1850.44 (1706.25- 1993.74); DALYs (95%CI, per 100,000 person-years), 99.69 (53.09-167.43), 28.06 (17.62-41.78), 3.93 (2.24-6.25). In addition, among the three dermatitis types, the greatest burden was associated with AD. According to the ASDR from 1990 to 2019, the burden of dermatitis has exhibited a slow downward trend in recent years. In 2019, the ASIR showed that the USA had the greatest burden, while the ASDR showed that Asian countries (such as Japan, Mongolia, Kazakhstan, and Uzbekistan) and some European countries (France, Estonia) had the greatest burden. According to SDI stratification and the three major dermatitis types, high ASIR and ASDR corresponded to high SDI areas (especially for AD). Conclusion The burden of dermatitis is related to socioeconomic development status, especially for AD, which is positively correlated with the SDI. The results based on GBD2019 data are valuable for formulating policy, preventing and treating dermatitis and reducing the global burden of dermatitis.